2022
DOI: 10.1044/2022_jslhr-22-00017
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Narrative Performance in Children With Developmental Language Disorder: A Systematic Review and Meta-Analysis

Abstract: Purpose: Narrative assessment is one potentially underutilized and inconsistent method speech-language pathologists may use when considering a diagnosis of developmental language disorder (DLD). However, narration research encompasses many varied methodologies. This systematic review and meta-analysis aimed to (a) investigate how various narrative assessment types (e.g., macrostructure, microstructure, and internal state language) differentiate children with typical development (TD) from children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 90 publications
4
20
0
2
Order By: Relevance
“…Forest plots will be inspected to visualize the extent of heterogeneity (by examining the width of confidence intervals and degree of overlap). A forest plot aligned with dependent effect sizes will be used, similar to Winters et al ( 2022 ). While we have already identified subgroup analyses which we believe will contribute to any possible heterogeneity, other subgroup analyses may be explored if needed (e.g., treatment type employed).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forest plots will be inspected to visualize the extent of heterogeneity (by examining the width of confidence intervals and degree of overlap). A forest plot aligned with dependent effect sizes will be used, similar to Winters et al ( 2022 ). While we have already identified subgroup analyses which we believe will contribute to any possible heterogeneity, other subgroup analyses may be explored if needed (e.g., treatment type employed).…”
Section: Methodsmentioning
confidence: 99%
“…Before conducting the analyses, we will check for outliers in the distribution of effect sizes. Outliers for the present review are effect size estimates that are more than three times outside the inter‐quartile range below the first quartile, or those more than three times the inter‐quartile range above the third quartile (Tukey, 1977 ; Winters et al, 2022 ). If outliers are present, we will conduct sensitivity analyses by removing these outliers and assess if this influences the results; if so, all analyses will be conducted with these outliers removed.…”
Section: Methodsmentioning
confidence: 99%
“…Narratives have also been used in previous studies with children with findings pointing to the relevance of investigating spoken language of children with reading difficulties [26]. Analysis of narrative language samples has been used to characterize the linguistic competence of a wide range of individuals including those diagnosed with developmental language disorders (DLD) [e.g., [27][28][29][30][31], with mixed results. These studies revealed that children with DLD were able to produce a cohesive, structured narrative discourse using a discourse task based on a picture book or a task where an adult listener saw or did not see a movie with the child and examining whether subjects altered their story [29,30].…”
Section: Narrativesmentioning
confidence: 99%
“…However, the children with reading difficulties showed significant difficulties in narrative ability compared to their peers without reading difficulties. Furthermore, a meta-analysis on oral narrative language measures of 37 studies between 1987 and 2019 confirmed significant narrative differences between children with and without language disorders [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation